THE IMPACT OF GOVERNMENT PSBB POLICY ON TRADISONAL MARKETS IN THE CITY OF SURAKARTA - Octaviani, Andri; Mulyadi, Mulyadi; Panglipurningrum, Yofhi Septian; Pahlawi, Lukman Ahmad Imron (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACTSince the outbreak of the Covid-19 virus in Indonesia, which began in March 2020, began to spread. The Covid-19 virus has had a significant impact on global conditions, not only in terms of the number of people who have died as a result of contracting the virus but also on the global economy. One of the affected nations, especially economically, is Indonesia. The Large-Scale Social Restrictions (PSBB) policy is one of the government's efforts to reduce the number of people who have become infected with the Covid-19 virus, and its effects are already being felt. The MSME sector of traditional market traders is included in the issued policies.In order to get input and evaluate the government's PSBB policy program or strategy in improving quality and sustainable PSBB regulatory policies, this study aims to analyze the implementation of the PSBB policy that is enforced on Traditional Market traders, including UMKM, during the Covid-19 pandemic.The SWOT (Strength, Weakness, Opportunity, Threat) matrix analysis was used in this study. In Surakarta, the SWOT matrix analysis is used to evaluate opportunities and threats as well as the advantages and disadvantages of government policies toward traditional markets.The research results show the impact that has occurred from the PSBB policy in Traditional Markets during Covid-19 is the decreased purchasing power of consumers resulting in traditional market traders closing their businesses, many are confused about policies that have not been consistent so that the income of traditional market traders has decreased. In overcoming this, the government is working on consistency, better dissemination of Government Policy (PSBB) so that traditional market traders do not experience many losses due to decreased income, as well as training human resources in the field of digital marketing so they are able to work to meet needs. The government is also trying to keep open access to traditional market sales for the economic stability of traditional market traders in the city of Surakarta.Keywords: PSBB, Traditional Market, Human Resources